Adult intussusception with multiple intestinal adhesions: A case report - Yopi Simargi, MD; Apriliani P. Dewi, MD; Resley O. Mulia, MD; Anita F. Puspasari, MD; Ayuningtyas Puspaningrum, MD; Ronny, MD; Fenny Susilo, MD (Radiology Case Reports, 2024)
Intussusception occurs when a part of the intestine enters another segment of the intestine causing bowel obstruction. It is common in children but not in adults with only <5% of prevalence of all intussusceptions. Most of the cases have an underlying neoplastic pathology. However, we found a case where an adult patient with 2 weeks of ileus obstruction is caused by intussusception with multiple intestinal adhesions. A 59-year-old man complained of being unable to defecate, or vomit and had a tender abdomen for 2 weeks. Contrast abdominal CT showed a dilated and thickened intestinal wall, with ileo-ileal intussusception in the distal terminal ileum, indicating a diagnosis of ileus obstruction due to intussusception. During laparotomy, intussusception was found but released spontaneously followed by ancillary findings were multiple adhesions in the ileum that caused the intussusception and obstruction. In conclusion, transient intussusception in adults with multiple adhesions has never been reported before, and a CT scan is an important clinical tool to diagnose and identify the cause of this condition. Recognizing the imaging abnormalities earlier is important to prevent further complications.